Does AI Reduce Physician Burnout? A Data-Driven Analysis of Digital Health Solutions - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2024)
Does AI Reduce Physician Burnout? A Data-Driven Analysis of Digital Health Solutions Physician burnout has reached epidemic proportions globally, posing...
Keywords: Digital Health; Diagnostics; Artificial Intelligence; Patient Care; Clinical Decision Support